The Role of Standards in Global Value Chains - Kaplinsky, Raphael (2012)
Standards have become an increasingly important dimension in global trade. Without the capacity to meet the growing body of standards, producers may either have difficulty in entering global markets, or be relegated to unprofitable and low-margin niches. This paper overviews the history of standards, explains the difference between different types of standards, and identifies the key stakeholders involved in the setting of standards. It then addresses the role that standards play in enterprise upgrading and considers some of the major costs for producers in meeting standards, including potential cost barriers for small-scale producers. Before concluding with a discussion of the policy challenges raised by these developments, it discusses the extent to which standards intensity in global value chains will be affected when the final markets increasingly move from high-income consumers in the North to lower-income consumers in Southern economies such as China and India.